Previous exposure to common coronavirus HCoV-NL63 is associated with reduced COVID-19 severity in patients from Cape Town, South Africa - Lesmes-Rodríguez, Lida C.; Lambarey, Humaira; Chetram, Abeen; Riou, Catherine; Wilkinson, Robert J.; Joyimbana, Wendy; Jennings, Lauren; Orrell, Catherine; Jaramillo-Hernández, Dumar A.; Schäfer, Georgia (Frontiers in Virology, 2023)
Background: Globally, the most significant risk factors for adverse COVID-19 outcome are increasing age and cardiometabolic comorbidities. However, underlying coinfections may modulate COVID-19 morbidity and mortality, particularly in regions with high prevalence of infectious diseases. Methods: We retrospectively analyzed serum samples for IgG antibodies against the common circulating coronaviruses HCoV-NL63, HCoV-229E, HCoV-OC43 and HCoV-HKU1 from non-hospitalized and hospitalized confirmed COVID-19 patients recruited during the first (June-August 2020) and second (October 2020-June 2021) COVID-19 wave in Cape Town, South Africa. Patients were grouped according to COVID-19 disease severity: Group 1: previously SARS-CoV-2 infected with positive serology and no symptoms (n=94); Group 2: acutely SARS-CoV-2 infected, hospitalized for COVID-19 and severe symptoms (n=92). Results: The overall anti-HCoV IgG seroprevalence in the entire patient cohort was 60.8% (95% CI: 53.7 – 67.8), with 37.1% HCoV-NL63 (95% CI: 30 – 44), 30.6% HCoV-229E (95% CI: 24 – 37.3), 22.6% HCoV-HKU1 (95% CI: 16.6 – 28.6), and 21.0% HCoV-OC43 (95% CI: 15.1 – 26.8). We observed a significantly higher overall HCoV presence (72.3% versus 48.9%) and coinfection frequency (43.6% versus 19.6%) in group 1 compared to group 2 patients with significantly higher presentation of HCoV-NL63 (67.0% versus 6.6%) and HCoV-HKU1 (31.1% versus 14.1%). However, only antibody titers for HCoV-NL63 were significantly higher in group 1 compared to group 2 patients (p < 0.0001, 1.90 [95% CI: 0.62 – 2.45] versus 1.32 [95% CI: 0.30 – 2.01]) which was independent of the participants’ HIV status. Logistic regression analysis revealed significantly protective effects by previous exposure to HCoV-NL63 [p < 0.001, adjusted OR = 0.0176 (95% CI: 0.0039 – 0.0786)], while previous HCoV-229E exposure was associated with increased COVID-19 severity [p = 0.0051, adjusted OR = 7.3239 (95% CI: 1.8195–29.4800)]. Conclusion: We conclude that previous exposure to multiple common coronaviruses, and particularly HCoV-NL63, might protect against severe COVID-19, while no previous HCoV exposure or single infection with HCoV-229E might enhance the risk for severe COVID-19. To our knowledge, this is the first report on HCoV seroprevalence in South Africa and its possible association with cross-protection against COVID-19 severity.